2023
DOI: 10.1021/acsapm.3c01755
|View full text |Cite
|
Sign up to set email alerts
|

Fish Scale Biomimetic Multifunctional Antifreeze Organogel for Flexible Strain Sensor Applications

Yanping Hao,
Jiao Li,
Chao Wang
et al.

Abstract: The applications of conductive hydrogels in the fabrication of wearable sensors have been highlighted in recent studies. However, water in traditional hydrogels is volatile at room temperature and readily frozen at subzero temperatures, resulting in material failure, which is critical in their practical applicability. In this paper, we prepared an organogel with sodium lignin sulfonate (Ls) and poly(vinyl alcohol) in a dimethyl sulfoxide and water dualsolvent system and embedded dense fish scale biomimetic clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Recently, with the latest developments in training theory, the ideal bandage is considered to be a porous soft material with directional tensile performance along the length direction that provides fixation pressure to an injured body part without hindering the normal movements of other body parts, i.e., offers comfortable and anisotropic-elastic function . As such, the development of such bandages has emerged as a prominent subject in the field of wearable medical devices , and soft robotics . Traditional elastic bandages are mainly made of poorly breathable elastic membranes, which result in unfortunate comfort when worn for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the latest developments in training theory, the ideal bandage is considered to be a porous soft material with directional tensile performance along the length direction that provides fixation pressure to an injured body part without hindering the normal movements of other body parts, i.e., offers comfortable and anisotropic-elastic function . As such, the development of such bandages has emerged as a prominent subject in the field of wearable medical devices , and soft robotics . Traditional elastic bandages are mainly made of poorly breathable elastic membranes, which result in unfortunate comfort when worn for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…To date, researchers have found that materials with low modulus can effectively reduce the ice shear strength. Gels are soft semisolid materials with excellent liquid storage capacity, giving them potential for use as anti-icing materials. Golovin et al conducted a study to design and predict the ice adhesion strength of numerous ice-repellent polymers, ultimately identifying organogels as the most effective choice due to their exceptionally low ice adhesion . Subsequently, considering their softness, hydrophobicity, and low elastic modulus, polysiloxane (PDMS)-based organogels by immersing PDMS-based networks in lubricants (silicone oil, perfluoroalkylether, and liquid paraffin) were developed to obtain low/ultra low ice adhesion strength, while they generally showed poor durability because of the loss of liquid lubricant during usage …”
Section: Introductionmentioning
confidence: 99%